Randomized phase I trial outcomes show safe and sustainable inhibition of classical and lectin complement pathways by empasiprubart - Inge Van de Walle; Laura Bracke; Heidi Gytz Olesen; Tonke van Bragt; Stéphanie Cadour; Phillip De Decker; Giorgia Ciurlia; Erwin Pannecoucke; Emma K. Persson; Olivier Van de Steen; Xinghong Leng; Gregers Rom Andersen; et al. (Nature Communications)
Abstract Activation of classical and lectin complement pathways contributes to several human diseases. Empasiprubart is a humanized recycling monoclonal antibody that inhibits both pathways by binding to the CCP2 domain of complement factor 2 (C2), an interaction that is dependent on both Ca2+ and pH. Here, we resolve the crystal structure of empasiprubart complexed with C2, providing the molecular basis of its Ca2+ dependency, and report a randomized, double-blind, placebo-controlled trial to assess the safety and tolerability (primary objectives) in addition to pharmacokinetics, pharmacodynamics, and immunogenicity (secondary objectives) of empasiprubart in 78 healthy participants (NCT04532125). A single intravenous (IV) dose of empasiprubart reduces circulating C2 levels by up to 99% and dose-dependently inhibits the classical and lectin pathways. Multiple IV empasiprubart doses reinforce reductions in free C2 levels, which persist until the endpoint of the study at 41 weeks. This prolonged reduction is in line with the empasiprubart elimination half-life (70–88 days). Single and multiple ascending doses of empasiprubart are generally safe and well tolerated. Overall, our results reveal in atomic detail the mechanism of empasiprubart and demonstrate that it is a first-in-class anti-C2 therapeutic antibody for use in complement-mediated diseases.